2022
DOI: 10.1002/jac5.1682
|View full text |Cite
|
Sign up to set email alerts
|

Deprescribing anticholinergics in primary care older adults: Experience from two models and impact on a continuous measure of exposure

Abstract: Background: Deprescribing interventions delivered through the electronic medical record have not significantly reduced the use of high-risk anticholinergics in prior trials. Pharmacists have been identified as ideal practitioners to conduct deprescribing; however, little experience beyond collaborative consult models has been published.Objective: To evaluate the impact of two pilot pharmacist-based advanced practice models nested within primary care. Methods: Pilot studies of a collaborative clinic-based pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Study strengths include the use of multiple criteria for PIM identification (Beers, STOPP, and ACB), which allowed for more nuanced PIM recognition. Previous studies utilized only one set of criteria for PIM recognition, potentially limiting PIM identification 15,20,27 . For example, several medications are listed on Beers and STOPP but not the ACB scale, including benzodiazepines and central alpha agonists (e.g., clonidine); while these are not anticholinergic, they can have significant CNS effects and caution should be taken in older adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Study strengths include the use of multiple criteria for PIM identification (Beers, STOPP, and ACB), which allowed for more nuanced PIM recognition. Previous studies utilized only one set of criteria for PIM recognition, potentially limiting PIM identification 15,20,27 . For example, several medications are listed on Beers and STOPP but not the ACB scale, including benzodiazepines and central alpha agonists (e.g., clonidine); while these are not anticholinergic, they can have significant CNS effects and caution should be taken in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing PIMs, particularly anticholinergics, may decrease risk of subsequent dementia, but it remains unclear whether this can improve cognitive function in the short‐term. A recent study found that two pharmacist‐led pilot anticholinergic deprescribing programs reduced the number of patients above a predefined “cognitive risk threshold,” but did not assess cognition as an outcome 15 . A review of interventions in patients with dementia concluded that anticholinergics were associated with greater all‐cause mortality, but cognitive effects were inconsistent 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation